MANAJEMEN SARANA DAN PRASARANA DALAM UPAYA MENINGKATKAN MUTU PENDIDIKAN - Nurazizah Azahra; Mardiyyah Nur Amatullah; Ahmad Fathur Rahman; Sulkifli (As-Sulthan Journal of Education, 2026)
This study examines the strategic management of educational of facilities and infrastructure withim the scope of institutional quality improvement. The objective of this research is to analyze how systematic infrastructure governance contributes to enhancing educational standards by utilizing a literature study method. This approach involves synthesizing data from academic journals, textbooks, and government regulations published withim the last decade. The results indicate that effective management relies on a comprehensive seven-stage cycle, including data-driven planning, accountable procurement, and digital-based inventory, which significantly fosters public trust and institutional accountability. Furthermore, the study highlights that well-maintained facilities, such as clean classrooms and functional laboratories, createva positive academic climate that boosts students' intrinsic motivation and learning outcomes. This research concludes that infrastructure management is an integral part of competitive quality assurance strategies in the modern era rather than just a technical logistic matter. These findings suggest that integrating digital management systems is essential for real-time monitoring and professionalism in addressing the gap between facility availability and curriculum needs.